A Model of Using Computer Vision to Monitor the Environment of a Collaborative Manipulator Robot - Yevsieiv, V.; Demska, N. (My University, 2024)
The paper considers a model of using computer vision to monitor the environment of a collaborative manipulator robot in the context of Industry5.0. The sequence of stages of image processing is described, including detection, tracking and classification of objects, which allows the robot to respond adaptively to changes in the environment and ensure safe interaction with a person. The model contributes to increasing the flexibility and efficiency of robotic systems in modern production processes
Keywords: Industry 5.0; computer vision; Collaborative manipulator robot; Environmental monitoring